2010
DOI: 10.1103/physreve.81.011403
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structural relaxation in a sheared supercooled colloidal liquid

Abstract: The rheology of dense amorphous materials under large shear strain is not fully understood, partly due to the difficulty of directly viewing the microscopic details of such materials. We use a colloidal suspension to simulate amorphous materials and study the shear-induced structural relaxation with fast confocal microscopy. We quantify the plastic rearrangements of the particles in several ways. Each of these measures of plasticity reveals spatially heterogeneous dynamics, with localized regions where many pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 96 publications
1
64
0
Order By: Relevance
“…Exponential tails in the pdf's of the displacement have been consistently observed in glassy and jammed systems, e.g. in sheared foams, 38 grains, 39 and colloids, 23 and even in simulations of molecular glass formers. 40 A general mechanism has been proposed to explain these exponential tails, 40 based on the idea that particles undergo discontinuous jumps.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Exponential tails in the pdf's of the displacement have been consistently observed in glassy and jammed systems, e.g. in sheared foams, 38 grains, 39 and colloids, 23 and even in simulations of molecular glass formers. 40 A general mechanism has been proposed to explain these exponential tails, 40 based on the idea that particles undergo discontinuous jumps.…”
Section: Discussionmentioning
confidence: 82%
“…This is an important limitation, since numerical simulations 22 have shown that rearrangements occur intermittingly in a threedimensional Lennard-Jones amorphous solid, a model system for soft particles. In this respect, optically microscopy is an attractive alternative to DWS, and it has been recently used to probe the yielding transition under oscillatory shear in both colloids 23 and emulsions 24 . The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the case of continuous shear, the microscopic dynamics in cyclically deformed amorphous solids have been found to be diffusive (or even subdiffusive), in simulations [18,19] as well as in experiments on colloids [2,20] or granular matter [21,22]. Aging effects have been reported for macroscopic quantities, e.g.…”
Section: Introductionmentioning
confidence: 91%
“…By contrast, the effect of a cyclic shear has been less investigated, in spite of its relevance to the fatigue tests commonly adopted in material science. Furthermore, cyclic deformation tests allow one to unambiguously identify irreversible rearrangements (as opposed to the non-affine displacement measured in continuous shear, which may be reversible) and to follow the evolution, or aging, of the dynamics as the sample is kept under an oscillatory deformation.Similarly to the case of continuous shear, the microscopic dynamics in cyclically deformed amorphous solids have been found to be diffusive (or even subdiffusive), in simulations [18,19] as well as in experiments on colloids [2,20] or granular matter [21,22]. Aging effects have been reported for macroscopic quantities, e.g.…”
mentioning
confidence: 91%
“…In contrast, it is much more difficult to identify the relevant defects that control the mechanical response in amorphous materials 1 . Disordered materials span a wide range of length scales from atomic systems, such as metallic glasses 2 and ceramics 3 , to colloidal suspensions 4,5 , and macroscopic particulate materials, such as foams [6][7][8][9] , emulsions 10 , and granular matter [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%